Riddles about everyday life as a reflection of ethnocultural identity (using the examples of Tuvan, Russian, and Colombian riddles) - Chesnokova, Olga S.; Radbil, Timur B. (The New Research of Tuva, 2024)
The article compares Tuvan, Russian, and Spanish-language (Colombian variant of Spanish) riddles related to daily life in the context of linguistic expression of ethno-cultural identity. The authors analyze the structural, rhetorical, and discursive means of presenting daily life in riddle texts and propose cognitive schemas for riddles about everyday life in three linguistic cultures. A comprehensive methodology for contrastive linguistic-cognitive ethnolinguistic-cultural description of riddles is employed, based on lexicosemantic and interpretative methods, as well as conceptual analysis, comparative analysis, and cultural commentary.It is revealed that the compared riddles present conceptual schemas of reification (objectification) and/or personification. These schemas are grounded in conceptual-metaphorical models that encode the enigmas as phenomena recognizable from the collective experience of the ethnic group’s linguistic engagement with reality, including natural phenomena, household objects, artifacts, zoomorphic and anthropomorphic entities, as well as their parts and/or attributes, along with dynamic frames that embody the standard functions of things or beings and the specifics of their activity.It is established that riddles about daily life, in the format of indirect nomination, implicitly reflect observations, experiences, associations, and real features of daily life. Together, these elements create a system of images of everyday life, embodying the culturally conditioned specifics of the world of daily existence.
Keywords: riddle of everyday life; game image; world of everyday life; ethnocultural identity; text of the riddle; comparative method; linguoculturology; linguistic cognitivism; Tuvan folklore; Russian folklore; Colombian folklore